THE FREE ALPHA AMINO NITROGEN CONTENTS OF SOME COMMON FOOD FISHES OF KAKINADA REGION , ANDRAPRADESH - GUPTA, SIBSANKAR; GOVINDAN, T K (Fishery Technology, 2017)
The moisture and free alpha amino nitrogen contents ofsome important food fishes and sheH fishes of Kakinada regionhave been studied. Crustacearis and molluscs contain free alphaamino acids in quantities several times higher than all otheraquatic animals examined in this study. Their probable rolein the physiological activities of these animals has been discussed